Integrating Organic Farming Practices in Horticulture: Impacts on Crop Quality and Marketability - M, Ranibai; Thriveni, Vangapandu; saikia, Nilaranjan; Nagarajan, K. (Journal of Neonatal Surgery, 2025)
Amid escalating concerns over agrochemical externalities, ecological degradation, and consumer health risks, organic horticulture has emerged as a scientifically grounded and ethically resonant alternative to conventional farming. This study offers a multidimensional assessment of organic farming practices applied to tomato, capsicum, and spinach, evaluating impacts across soil quality, crop physiology, nutritional biochemistry, post-harvest behavior, consumer perception, and economic viability under Indian agroecological conditions. Employing a randomized block design with rigorous field and lab-based analyses, results revealed that organically managed plots exhibited superior soil organic carbon, microbial biomass, and nutrient availability, affirming the regenerative potential of bio-inputs. Although yields were slightly lower, crops under organic cultivation demonstrated enhanced morphological vigor, reduced pest incidence, and greater physiological uniformity. Biochemical assays indicated significantly elevated levels of vitamin C, antioxidants, and phenolics in organic samples, alongside reduced nitrate residues and prolonged shelf stability. Consumer surveys highlighted a strong market preference for organically labeled produce—especially under simplified “chemical-free” branding—with 64% willing to pay a premium. Furthermore, economic evaluations demonstrated higher net returns per hectare in organic systems due to lower input costs and elevated farmgate and retail prices. These findings not only validate the ecological and nutritional superiority of organic horticulture but also reposition it as an economically rational strategy for smallholder and market-driven farming systems. The study advocates for policy and institutional support to expand localized certification, strengthen direct-market infrastructures, and invest in transparency-enhancing technologies to accelerate the mainstreaming of organic horticulture in global agri-food systems.